What drives university engineering students to become entrepreneurs? Finding different recipes using a configuration approach. (4th March 2023) - Rippa, Pierluigi; Ferruzzi, Gabriella; Holienka, Marian; Capaldo, Guido; Coduras, Alicia
ABSTRACT: This research aims to investigate how combinations of factors lead to the entrepreneurial intention and propensity of engineering university students. The study proposes the application of a configuration approach (Qualitative Comparative Analysis) with a sample of 10, 008 engineering students from 43 universities in 10 European countries. The findings show that entrepreneurial intention and propensity do not depend only on a single driver but on the interplay of multiple factors. The intensity of entrepreneurship education is a necessary but not sufficient condition. Different recipes brought to light in the analysis belong to similar socioeconomic contexts.